HUBUNGAN DUKUNGAN SOSIAL DAN TINGKAT STRESS DENGAN KEJADIAN BURNOUT PADA FAMILY CAREGIVER LANSIA DI KELURAHAN CIAPUS BOGOR - Indira Cahyani (2023)
The amount of burden borne by family caregivers is one of the negative things about caring for the elderly, and if they don't get social support it will impact stress which can trigger the onset of burnout. This study aims to determine the relationship between social support and stress levels with the incidence of burnout in elderly family caregivers in Ciapus Village, Bogor. The method used was cross-sectional using Chi-Square test to determine the relationship between variables such as social support, stress levels, and burnout. The sampling technique used was stratified random sampling on 222 elderly family caregivers. The instruments used are MSPSS (The Multidimensional Scale of Perceived Social Support), KCSS (Kingston Caregiver Stress Scale), and MBI-HSS (Maslach Burnout Inventory-Human Service Survey). This study shows that there's a relationship between social support and stress with burnout with a p-value of 0.000 and 0.000 which means p<0.05. It is hoped that health service providers will provide support for family caregivers and conduct counseling programs related to stress or burnout so that families can provide the best care so that the quality of life of the elderly increases. The findings in this study clarify the previous findings and add further information so that future researchers can conduct research related to other factors that can affect burnout in elderly family caregivers.